Experimental study on preparedness of disease X with an agent-based framework scenario-driven analysis - Dmytro Chumachenko (Радіоелектронні і комп'ютерні системи, 2025)
Emerging respiratory pathogens continue to impose substantial health and economic burdens worldwide, motivating generic readiness tools that do not rely on pathogen-specific data. This study investigates how five archetypal stressors, namely, rising antivaccine misinformation, behavioural fatigue, vaccine supply disruption, immune escape variant emergence, and armed conflict infrastructure collapse, reshape the course of a hypothetical high-consequence agent designated Disease X. The study’s objective is to quantify each shock’s epidemiological impact in an otherwise identical urban population and to identify the systemic vulnerabilities that most threaten early outbreak control. Addressing that objective required the following tasks, which began with a critical review of scenario-based epidemic modelling, progressed to the extension of a validated SEIRDV agent-based core with dynamic belief diffusion, dose-queue logistics, and conflict-driven mobility, and provided experiments per scenario using parameters anchored in peer-reviewed evidence. The framework shows that a 15% point surge in antivaccine belief doubles the peak prevalence and adds 258 deaths. A 50-point erosion of masking and distancing produces a secondary wave that still trims by 9% after fatigue re-engagement. A 70 % mRNA supply shortfall lasting 35 days increases deaths by 7%, and seeding 50 immune-escape cases (R0≈9.5, 60 % neutralization loss) increases cumulative mortality by 41 % within six weeks. The composite conflict shock elevates deaths by 71 % despite a 10% population outflow. These non-linear responses arise solely from changes in behaviour, logistics, or context, as biological constants remain fixed. The findings demonstrate that preparedness cannot rely on any single lever. Effective mitigation demands synchronized risk communication, staged behavioural support, diversified and buffered manufacturing capacity, rapid antigenic update pathways and humanitarian vaccination corridors. This study supplies a decision support instrument for stress-testing policy portfolios before the next high-consequence outbreak.